1994
DOI: 10.1128/jb.176.19.5888-5896.1994
|View full text |Cite
|
Sign up to set email alerts
|

Response to UV damage by four Escherichia coli K-12 restriction systems

Abstract: To understand the role of restriction in regulating gene flow in bacterial populations, we would like to understand the regulation of restriction enzyme activity. Several antirestriction (restriction alleviation) systems are known that reduce the activity of type I restriction enzymes like EcoKI in vivo. Most of these do not act on type II or type Ill enzymes, but little information is available for the unclassified modificationdependent systems, of which there are three in E. coli K-12. Of particular interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 78 publications
2
33
1
Order By: Relevance
“…Earlier studies suggested that W3110, the E. coli strain used in these studies, may carry an asyet-uncharacterized restriction system active against T-even phages (13). This may explain some of the differences between our results and those of previous reports (2,7,8). However, as McrB is moderately sensitive to the ClpAP protease, this may also help to reconcile results concerning RA in previous publications (2,7,8 …”
contrasting
confidence: 57%
“…Earlier studies suggested that W3110, the E. coli strain used in these studies, may carry an asyet-uncharacterized restriction system active against T-even phages (13). This may explain some of the differences between our results and those of previous reports (2,7,8). However, as McrB is moderately sensitive to the ClpAP protease, this may also help to reconcile results concerning RA in previous publications (2,7,8 …”
contrasting
confidence: 57%
“…It is not known whether RA can be achieved by proteases other than ClpXP or by mechanisms other than proteolysis. RA has been demonstrated for a type III system and for a methylation-dependent system but is not a characteristic of type II systems (81).…”
Section: Host-controlled Modulation Of Restriction Activitymentioning
confidence: 99%
“…To circumvent this burden, the organism appears to control the intracellular enzyme concentration. As shown for E. coli, efficient phage restriction occurs by using about 60 molecules of EcoKI, which would consume ϳ0.2% of the total ATP pool (86,87).…”
Section: Fitness Cost Incurred By R-m Systems On Host Bacteriamentioning
confidence: 99%